In Vivo Measurement of Surface Pressures and Retraction Distances Applied on Abdominal Organs During Surgery. (February 2018) - Shah, Dignesh; Alderson, Andrew; Corden, James; Satyadas, Thomas; Augustine, Titus
This study undertook the in vivo measurement of surface pressures applied by the fingers of the surgeon during typical representative retraction movements of key human abdominal organs during both open and hand-assisted laparoscopic surgery. Surface pressures were measured using a flexible thin-film pressure sensor for 35 typical liver retractions to access the gall bladder, 36 bowel retractions, 9 kidney retractions, 8 stomach retractions, and 5 spleen retractions across 12 patients undergoing open and laparoscopic abdominal surgery. The maximum and root mean square surface pressures were calculated for each organ retraction. The maximum surface pressures applied to these key abdominal organs are in the range 1 to 41 kPa, and the average maximum surface pressure for all organs and procedures was 14 ± 3 kPa. Surface pressure relaxation during the retraction hold period was observed. Generally, the surface pressures are higher, and the rate of surface pressure relaxation is lower, in the more confined hand-assisted laparoscopic procedures than in open surgery. Combined video footage and pressure sensor data for retraction of the liver in open surgery enabled correlation of organ retraction distance with surface pressure application. The data provide a platform to design strategies for the prevention of retraction injuries. They also form a basis for the design of next-generation organ retraction and space creation surgical devices with embedded sensors that can further quantify intraoperative retraction forces to reduce injury or trauma to organs and surrounding tissues.